The Trade Saga between Land of Uncle Sam VS Land of Bamboo Curtain - Angelin, Margareta Sevilla Rosa; Farun, Deforty Jihan; Putri, Farida Danas; Michael, Tomy (Budapest International Research and Critics University, 2021)
The purpose of this journal is to prove the facts that occurred during the trade war between the United States and China, which will then bring out solutions that can be offered to major problems between the two countries. Based on the facts, both in the form of chronology and the impact arising from the trade war, this research can narrow the distribution of the data and draw a common thread to see what solutions are offered, so that there is no overlap between the news and the facts. Starting from a cooperative relationship between the two countries, which then led to disputes and even tensions between them. Not infrequently in bilateral relations, there can be trade wars between the two countries. Such as comments on the trade war that occurred between the United States and China.